Драматичний діалог у творчості Лесі Українки - Левчук, Юлія Олександрівна; Levchuk, Yuliia O. (Тбіліський державний університет імені Іване Джавахішвілі, Інститут україністики, 2014)
The paper considers the problem of genre in the creative work of Lesya Ukrainka, in particular, small dramatic genres. We should take into account the dramatic dialogue as a syncretic genre, which includes signs of philosophy (Socratic) dialogue and drama as a genre. The material used in the study were such works as – “Farewell” (1896), “Three Minutes” (1905), “In The House of work, In The Country of bondage” (1906) and “Aisha and Mohammed” (1907). The methodological basis of intelligence was a cognitive approach to the study of genre and theory.
The Dramatic Dialogue in the Works of Lesya Ukrainka
Keywords: малі драматичні жанри; small dramatic genres; драматичний діалог; dramatic dialogue; когнітивна жанрологія; cognitive genre theory